(untitled) (Bangladesh Journal of Medical Science, 2014)
Objective: The main objective of this research is to explore the positive consequences of parents mental illness on their children. Material & methods: This study was a part of a more comprehensive study performed based on grounded theory. In this work semi-structured interviews were conducted with 17 participants selected by purposeful and theoretical sampling approach. Data were analyzed using constant comparative analysis suggested by Straus and Corbin (1988) method. Results: Despite negative effects of the illness, the children have been perceived positive effects from their parents illness. These findings categorized in two category of "independence" and "considering the others needs". Conclusion: Application of these findings in care plan of patients and families, particularly their children, can offer more efficient coping with mental illness. DOI: http://dx.doi.org/10.3329/bjms.v13i4.12989 Bangladesh Journal of Medical Science Vol.13(4) 2014 p.449-453